2014
DOI: 10.1074/jbc.m113.540682
|View full text |Cite
|
Sign up to set email alerts
|

Mice Lacking Selenoprotein P and Selenocysteine Lyase Exhibit Severe Neurological Dysfunction, Neurodegeneration, and Audiogenic Seizures

Abstract: Background: Selenoproteins play a critical role in neuroprotection. Results: Deletion of selenocysteine lyase (Scly) in combination with selenoprotein P (Sepp1) further aggravates the phenotype of Sepp1 Ϫ/Ϫ mice, as Scly Ϫ/Ϫ Sepp1 Ϫ/Ϫ mice have impaired survival and surviving mice exhibit neurological dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 39 publications
3
48
0
Order By: Relevance
“…The canonical pathways significantly affected by AC-T treatment were molybdenum biosynthesis and selenocysteine biosynthesis which are both involved in redox reactions [33,34]. Fatty acid activation was also affected which can occur in the outer mitochondrial membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The canonical pathways significantly affected by AC-T treatment were molybdenum biosynthesis and selenocysteine biosynthesis which are both involved in redox reactions [33,34]. Fatty acid activation was also affected which can occur in the outer mitochondrial membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Selenocysteine lyase-knockout mice are viable when fed diets that are not severely selenium deficient (92). However, mice with selenium deficiency in their brains, caused by knockout of the selenium transport protein Sepp1 (45,90), develop severe neurological injury and die when selenocysteine lyase is knocked out simultaneously (23). Thus, selenocysteine lyase protects brain neurons under selenium-deficient conditions, presumably by facilitating reutilization of their selenium (Figure 2).…”
Section: The Intracellular Selenium Cyclementioning
confidence: 95%
“…Another line of evidence has demonstrated that oxidative stress impairs PV-interneuron development and functionality [66, 67, 160]. Along a similar vein, several studies in selenoprotein knockout mice have reported deficits in PV-interneurons [65, 68, 113], presumably due to diminished antioxidant defense capabilities. Moreover, a microarray study examining gene expression in postmortem prefrontal cortex tissue found that SelP levels were significantly lower in subjects with schizophrenia [161].…”
Section: Selenium Selenoproteins and Neurological Diseasementioning
confidence: 98%
“…These results suggest that Scly-mediated Sec recycling becomes physiologically important only when dietary Se supply is not adequate. To obtain insight into the relationship between Scly and SelP in selenium metabolism, double knockout mice lacking both of the aforementioned genes were generated and characterized [113]. Scly −/− SelP −/− mice required selenium supplementation to survive, and surviving mice exhibited impaired motor coordination, audiogenic seizures, and neurodegeneration in brainstem regions akin to those previously reported for ApoER2 −/− and SelP −/− mice fed Se-deficient diets [90].…”
Section: Constitutive Knockout Mice Studiesmentioning
confidence: 99%